Genetic diversity and structure in Austrocedrus chilensis populations:implications for dryland forest restoration - Souto, Cintia Paola (2012)
In South America, 94% of dry-temperate lands present some degree of environmental degradation, highlighting the need for ecological restoration. We analyzed geographic patterns of genetic variation in Austrocedrus chilensis, a dominant conifer of the steppe-forest ecotone in the eastern Andes, to examine its potential for restoration. We sampled 67 locations in Argentina and estimated genetic parameters to determine the effects of historical factors affecting diversity, together with inbreeding and gene flow, using 12 allozyme loci. Genetic diversity decreased southwards in eastern populations, which are marginal for the range of the species and patchily distributed, while high genetic admixture was detected in continuous western populations, possibly reflecting postglacial migrations from northern and eastern sources. Higher inbreeding (F IS > 0.14) was recorded in northern compared with southern populations, attributed to the impact of recent bottlenecks resulting from anthropogenic fires. Gene flow was found to be moderate overall (F ST = 0.12). The implications of these results for restoration actions focusing on Austrocedrus were explored. Relatively small, inbred yet genetically diverse northern populations should be the subject of passive restoration efforts, while experimental common gardens should be established toward the south, to support active restoration approaches. This illustrates how ahead of time information on patterns of genetic variation can support restoration efforts for dryland tree species. © 2011 Society for Ecological Restoration International.